2008
DOI: 10.1074/jbc.m708165200
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of Phycobiliproteins

Abstract: The Synechococcus sp. PCC 7002 genome encodes three genes, denoted cpcS-I, cpcU, cpcV, with sequence similarity to cpeS. CpcS-I copurified with His 6 -tagged (HT) CpcU as a heterodimer, CpcSU. When CpcSU was assayed for bilin lyase activity in vitro with phycocyanobilin (PCB) and apophycocyanin, the reaction product had an absorbance maximum of 622 nm and was highly fluorescent ( max ‫؍‬ 643 nm). In control reactions with PCB and apophycocyanin, the products had absorption maxima at 635 nm and very low fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…are ␤Cys 82 -DHBV and most likely a ␤Cys 82 -PEB with an altered, incorrect configuration or conformation. Indeed, nonenzymatic addition of bilins to other phycobiliproteins was shown to be inefficient and to produce oxidized side products (11,35,38,39,46,53). In the case of CpcA, CpcB, PecA, and PecB from Mastigocladus laminosus, PCB adds spontaneously to the correct Cys 84 binding site but in a non-native configuration (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…are ␤Cys 82 -DHBV and most likely a ␤Cys 82 -PEB with an altered, incorrect configuration or conformation. Indeed, nonenzymatic addition of bilins to other phycobiliproteins was shown to be inefficient and to produce oxidized side products (11,35,38,39,46,53). In the case of CpcA, CpcB, PecA, and PecB from Mastigocladus laminosus, PCB adds spontaneously to the correct Cys 84 binding site but in a non-native configuration (54).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, only members of groups CpcS-I, CpcS-III, and CpcU were well (38,39,46). 4 While the function of CpcV group lyases is enigmatic, S-type lyases of groups CpeS and CpeU were speculated to attach PEB to PE subunits, due to their encoding in gene clusters associated to PE maturation (45).…”
Section: Discussionmentioning
confidence: 99%
“…PCC 7002 and Anabaena sp. PCC 7120 (Saunee et al 2008;Shen et al 2008;Zhao et al 2007). Phylogenetic analyses of cyanobacteria based on their PCB lyases suggested that the heterodimeric lyases CpcS-1 and CpcU are also responsible for PCB attachment in Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 This latter approach required the multi-plasmid-based production of: (i) the apoprotein, (ii) heme oxygenase, (iii) one or more reductases required to generate the chromophore from biliverdin, and (iv) one or more lyase(s). [19][20][21] A somewhat simplified approach reducing the number of plasmids required for transformants capable of producing biliproteins has recently been demonstrated. 22 It is based on expressing the structural gene fused to genes coding for chromophore biosynthesis from endogenous heme.…”
Section: Introductionmentioning
confidence: 99%